Peak performance: Characteristics and key factors in the development of the world top-8 swimmers based on longitudinal data - Chen, Y.; Huang, C.; Chen, H.; Huang, T.; Su, C.; Chen, J. (International Journal of Sports Physiology and Performance, 2024)
Purpose This study aimed to investigate the peak performance characteristics of the world top-8 swimmers and the key factors involved in the journey toward achieving better peak performance.